Rediscovery of Mimoniades baroni (Godman & Salvin, 1895) (Lepidoptera: Hesperiidae: Pyrrhopyginae) - Lamas, Gerardo (2004)
The rediscovery of Mimoniades baroni (Godman & Salvin, 1895) (Lepidoptera: Hesperiidae: Pyrrhopyginae), in Cajamarca, Peru, is reported herein. The species had not been recorded since its original description, almost 110 years ago.